STRATEGI PEMBANGUNAN EKONOMI YANG ISLAMI MENURUT FAHIM KHAN - Ali Murtadho (Economica: Jurnal Ekonomi Islam, 2016)
Several theories about the development strategy formulated by the most conventional neo-classical economists much criticized. Fahim Khan including contemporary Islamic economic thinkers who criticize conventional economic development strategy with alternative bids from the Islamic economics perspective. Their thinking is exciting to examined substance and its correlation with the economic development of contemporary Islamic discourse that dominated the development of financial institutions/syariah banking. The creation of entrepreneurial opportunities made Fahim Khan as a keyword in the concept of criticizing conventional strategy and supporting the Islamic economic development strategy. Strategy opened and graced this productive creative independent businesses are deemed appropriate and supported by the Islamic economic system based on profit and loss sharing partnership (profit-loss sharing). The idea is to promote excellence banking system of sharing based on the conventional interest-based banking system in spurring economic development suplus to enliven the entrepreneurial workforce.